DOI: 10.29007/dvlw
|View full text |Cite
|
Sign up to set email alerts
|

An Initial Investigation of Student Experiences with the Elements of High Impact Educational Practices

Abstract: As Universities attempt to elevate the student experience, one approach has been the formalization of a series of effective educational practices, termed High Impact Educational Practices (HIEPs). This study considers one university in the Southeastern U.S. that measures the quantity and quality of HIEPs based on the experiences of graduating undergraduate construction management (CM) students. The study addresses four different types of HIEPS: study abroad, internships and co-ops, undergraduate research, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Many studies have explored and verified the positive impact that HIPs have on students' persistence, cognitive and noncognitive educational attainment, and academic achievements (e.g., Brownell & Swaner, 2010;Farrow et al, 2021;Kilgo et al, 2015;Morris et al, 2019;White, 2018). Kuh (2013) found that, among college seniors in America, HIPs are positively and significantly correlated with students' self-reported gains across several dimensions of learning, such as inquiry and analysis, critical thinking, written and oral communication skills, and quantitative literacy.…”
Section: Hips Among American Undergraduatesmentioning
confidence: 99%
“…Many studies have explored and verified the positive impact that HIPs have on students' persistence, cognitive and noncognitive educational attainment, and academic achievements (e.g., Brownell & Swaner, 2010;Farrow et al, 2021;Kilgo et al, 2015;Morris et al, 2019;White, 2018). Kuh (2013) found that, among college seniors in America, HIPs are positively and significantly correlated with students' self-reported gains across several dimensions of learning, such as inquiry and analysis, critical thinking, written and oral communication skills, and quantitative literacy.…”
Section: Hips Among American Undergraduatesmentioning
confidence: 99%